Heavy Metals Content in Phaeophyceae from Malang Rapat Waters, Bintan - Hilda Novianty; Emienour Muzalina Mustafa; Suratno Suratno (Marine Science Department Diponegoro University, 2021)
The use of brown-macroalgae (Phaeophyceae) as an alginate source is very broad, covering the food and non-food industry, because of that it is necessary to know the safety of these natural resources, one of which is safe from heavy metal contamination. The purpose of this study was to determine heavy metals concentrations accumulated in several types of Phaeophyceae (brown macroalgae) as an alginate source from Malang Rapat waters, Bintan. The method used was descriptive non-experimental. The determination of the location of sampling was done by purposive sampling method. Samples were taken through free collection, identified species and measured of metal contamination concentrations for As, Cd, and Pb. The data obtained were analyzed descriptively. The results showed that Phaeophyceae found in Malang Rapat waters were Turbinaria conoides, Sargassum aquifolium, Padina australis, Hormophysa cuneiformis with each metal concentration contamination of As 13.95 to 23.30 µg.g-1 dry weight; Cd from 0.33 to 1.08 µg.g-1 dry weight and Pb from 4.72 to 9.92 µg.g-1 dry weight. This study showed that all metal contamination ranges in all Phaeophyceae were on the verge of the maximum limit set by the National Standardization Agency of Indonesia Indonesian (SNI) No 7387 of 2009 and National Agency of Drug and Food Control of RI (BPOM) Regulation No 5 of 2018 for dried macroalgae product so that Phaeophyceae from Malang Rapat waters - Bintan was not safe to be used as raw material for alginate source or other processed products of brown-macroalgae.